2020
DOI: 10.3390/nu12030825
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors in Relation to Liver Fat Content: A Cross-sectional Study

Abstract: Non-alcoholic fatty liver disease (NAFLD) can lead to functional liver impairment and severe comorbidities. Beyond energy balance, several dietary factors may increase NAFLD risk, but human studies are lacking. The aim of this cross-sectional study was to investigate the associations between food consumption (47 food groups, derived Mediterranean and Dietary Approaches to Stop Hypertension (DASH) diet quality scores) and liver fat content (continuous scale and NAFLD, i.e., >5% liver fat content). Liver fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
(55 reference statements)
2
14
0
Order By: Relevance
“…The nested case-controls analysis carried out within the multiethnic cohort that involved 2959 NAFLD cases (509 with cirrhosis and 2450 without cirrhosis) and 29,292 matched controls showed that higher DASH scores were inversely associated with NAFLD risk [ 64 ]. In agreement, the DASH score was related to lower liver fat content and NAFLD in a recent cross-sectional study [ 65 ].…”
Section: Nutritional Management Of Nafldsupporting
confidence: 67%
“…The nested case-controls analysis carried out within the multiethnic cohort that involved 2959 NAFLD cases (509 with cirrhosis and 2450 without cirrhosis) and 29,292 matched controls showed that higher DASH scores were inversely associated with NAFLD risk [ 64 ]. In agreement, the DASH score was related to lower liver fat content and NAFLD in a recent cross-sectional study [ 65 ].…”
Section: Nutritional Management Of Nafldsupporting
confidence: 67%
“…A recently published study by Watzinger et al evaluated the dietary factors that affect the liver fat content. They observed that a higher intake of high-fat dairy, such as sour cream in our study, is associated with non-alcoholic fatty liver disease, thus increasing the liver function tests, results that were in accordance with ours [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a systematic review and meta-analysis reported that DASH might be a better choice for weight management and reduction than other low-energy diets [ 159 ]. Some observational studies suggest that this diet could play a preventive role in NAFLD [ 160 , 161 ].…”
Section: Nutrition and Nafldmentioning
confidence: 99%